Development of Asahan River Tourism Activities in Support of National Tourism Strategic Area of Lake Toba - Prawira, Mega Fitriani Adiwarna; Budisetyorini, Beta; Adisudharma, Deddy; Salam, Dicky Arsyul; Wulandari, Wisi; Susanto, Eko (Politeknik Negeri Bandung, 2021)
Following up on the Development of The National Tourism Strategic Area of Lake Toba, which was directed in the study